PENGEMBANGAN LDS YANG DIAWALI PETA KONSEP PADA MATERI SISTEM PERNAPASAN PADA MANUSIA UNTUK SMP - Wulandari, Pratiwi; Risdawati, M.Si., Renny; Nerita, S.Pd, M.Pd, Siska (Pendidikan Biologi, 2014)
ABSTRACT   Teaching  material  is  all  of  material  (such  information,  tool,  although  texts)  which arranged in systematic, that show the intact form of competencies will dominate by the student and using in learning proces with the purpose planning and implementing of learning. LDS  is each of teaching material that prepare by the teacher for students in achievement the goals of learning. Dealing with observation and interview toward teacher and student that in SMPN 22 Padang, already used LDS in learning process. LDS that using is less interest the student attention. The caused is LDS has unclear picture, unclear instruction and LDS do not have clear explanation, at the result the students get confuse in doing activity. The purpose of this research is to resulted LDS that begin with concept map in respiration system material at humans which valid and practice. The reseach of LDS development that begin with concept map in respiration system at humans, develop  with  using  model  4-D,  cousist  of  the  define  step,  design  step,  develop  step,  and disseminate step, but this research only in develop step.The result of the research have been got, the validity to ward lecturer and teacher around 85,16% with some aspect of validity criteria didactic, construction and  technique, meanwhile in  practicalitas value toward teacher  around85,27% with practical criteria and view of student interest and show the picture in conclusion, LDS that resulted was valid and very practice.